Successful Aging among Older Adults Using Computers: a Systematic Review - Ali Saare, Murtaja; Hussain, Azham; ., . (International Journal of Engineering and Technology, 2018)
Recently, most of the previous studies focused on technology use and adoption among adults. However, few studies have been conducted on older adults. More specifically the emphasis is on the problems in different areas i.e. health care, housing, education, employment, and product design. Therefore, in this study, a systematic literature is taken into account where it includes multiple databases with a cut-off starting point of 2007 to 2017 that empirically examined predictors of successful aging of older adults to investigate current empirical studies. This study found that the use technology such as automatic teller machines (ATM) or VCRs are the predictor of use of computers. Moreover, older adults are likely to adopt to new technology when they recognize potential benefits. It is expected that the consolidated literature will serves as a guideline for future studies.